2023
DOI: 10.1002/cctc.202201488
|View full text |Cite
|
Sign up to set email alerts
|

Concepts of Computational Approach to Explore Heterogeneous Catalysts for Direct Methane Conversion

Abstract: The nonoxidative coupling of methane has attracted much attention because it yields two useful products: ethane and hydrogen. However, low conversion at low temperatures and carbon deposition at high temperatures are considered problematic. In this Concept article, a solution to these problems is presented. On the basis of the reaction enthalpy for the initial C−H bond cleavage of methane and the energy difference between C1 species (CH3 and CH) on the catalyst surface, a catalyst search guideline is provided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 70 publications
0
1
0
Order By: Relevance
“…Furthermore, the study revealed how nanoparticle size alters the ratio between these exposed surfaces and their respective significance in catalytic properties. The activity dependency on nanoparticle size was found to be closely linked to surface characteristics [132,133]. At smaller particle sizes, the dominance of the M(211) surface exposure was noted, whereas larger particles saw increasing contributions from M (111) and M(100).…”
Section: Comparative Analysis With Traditional Catalystsmentioning
confidence: 91%
See 1 more Smart Citation
“…Furthermore, the study revealed how nanoparticle size alters the ratio between these exposed surfaces and their respective significance in catalytic properties. The activity dependency on nanoparticle size was found to be closely linked to surface characteristics [132,133]. At smaller particle sizes, the dominance of the M(211) surface exposure was noted, whereas larger particles saw increasing contributions from M (111) and M(100).…”
Section: Comparative Analysis With Traditional Catalystsmentioning
confidence: 91%
“…However, the en-ergetics favored M(211) over M (111), and the activity of M(100) was limited by surface site blockage. Consequently, larger particles exhibited reduced activity due to the lower activity of M(100) and M (111) surfaces when compared to M(211) [129][130][131][132][133]. In terms of metal-dependent activity, the study found that Rh exhibited the highest activity, followed by Ni, and then Pd and Pt, which showed similar levels of activity.…”
Section: Comparative Analysis With Traditional Catalystsmentioning
confidence: 94%
“…A field called catalytic informatics is emerging. Several review and concept articles have been written on this field. Indeed, a wide variety of informatics methods are becoming available to aid in catalyst development.…”
Section: Introductionmentioning
confidence: 99%